Structural Robustness and Disproportionate Collapse in Buildings (2nd Edition) - Haynes R (Institution of Structural Engineers (ISTRUCTE), 2023)
The first edition (2010) provided a background to the fundamental attributes of robustness and an interpretation of, and practical guidance to, the regulations being followed in the UK at the time (primarily British Standards). This second edition (2023) builds on the first, to be fully-aligned with the Eurocodes - with a particular focus on BS EN 1991-1-7 - and the Building Safety Act. It contains new chapters on the subjects of 'Risk', 'Design of structural alterations to existing buildings', 'Classification of buildings', and 'The risk of disproportionate collapse in fire'. It also considers 'light steel frame' as a material distinct from steel. There is an emphasis on modern methods of construction (MMC) and a selection of new case studies.